Potential geo-discriminative tools to trace the origins of the dried slices of shiitake (Lentinula edodes) using stable isotope ratios and OPLS-DA. (15th October 2019) - Chung, Ill-Min; Kim, Jae-Kwang; Han, Jae-Gu; Kong, Won-Sik; Kim, So-Yeon; Yang, Yu-Jin; An, Yeon-Ju; Kwon, Chang; Chi, Hee-Youn; Yhung Jung, Mun; Kim, Seung-Hyun
Highlights: δ 13 C, δ 15 N, δ 18 O, and δ 34 S varied significantly with country of origin ( P  < 0.05). Externally validated test provided an excellent predictability ( Q 2 cum  = 0.881). δ 18 O and δ 15 N were the best indicators for shiitake origin discrimination. The probability of wrong classification of geographical origin was the below 1.2%. Abstract: The Lentinus edodes species, known as shiitake, has a history of extensive use in many cuisines in several East Asian countries owing to its unique and pleasant flavor and texture. As international food trade increases, reliable discrimination of geographical origin is becoming increasingly crucial in Korea to identify cheaper imported Chinese shiitake. Herein, stable isotope ratios (i.e., δ 13 C, δ 15 N, δ 18 O, and δ 34 S) were measured with a stable isotope ratio mass spectrometer, and a geographical discrimination method using orthogonal projection to latent structure-discriminant analysis was developed. The externally validated discrimination method showed excellent predictability ( Q 2 cum  = 0.881) and illustrated that δ 18 O and δ 15 N were important isotope markers for the geographical discrimination of dried shiitake slices. This study extends the knowledge of geographical differences between China and Korea evidenced by the shiitake isotope signatures, thereby contributing to potential geographical authentication with broader applications for international shiitake markets.